Khao co hoc Binh Duong tur tien su den so su - Bui, Chi Hoang; Nguyen, Van Quoc; Nguyen, Khanh Trung Kien (Nha xuat ban Khoa hoc xa hoi, 2010)
Archaeological sites and artifacts found in Binh Duong Province, Vietnam.